METHODS OF FORMATION OF TERMS - Islamova Ezoza Yorkin kizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract. This article provides a brief overview of the formation and construction of economic terms. Moreover, the article considers economic terminology in terms of justification and construction based on simple terms and examples.